Modern Antiplatelet Therapy for Percutaneous Coronary Intervention. How to Make the Right Choice? - T. M. Uskach; A. S. Tereshchenko (Рациональная фармакотерапия в кардиологии, 2020)
Dual antiplatelet therapy is the most important step in acute coronary syndrome (ACS) treatment. The new generation of inhibitors of P2Y12 platelet receptors (prasugrel and ticagrelor) provide more pronounced platelet inhibition than clopidogrel. The drugs differ in pharmacodynamics and platelet reactivity tests due to different mechanisms of binding to P2Y12 receptors. The antiplatelet effect of prasugrel and ticagrelor provides clinical benefit and better prognosis in patients with various forms of ACS. In patients with ST-segment elevation ACS prasugrel and ticagrelor are preferred over clopi-dogrel due to their higher efficacy and better clinical outcomes, and currently have preferential positions in guidelines compared to clopidogrel. The comparison of prasugrel versus ticagrelor (ISAR-REACT 5 trial) demonstrated superiority of prasugrel over ticagrelor in patients with ST-segment elevation ACS, for whom an invasive evaluation is planned and in early invasive treatment non-ST-segment elevation ACS. The choice of a drug for dual antiplatelet therapy in various clinical situations remains controversial. The latest ESC guidelines on non-ST elevation ACS (2020) [1] demonstrate the possible preference for prasugrel in patients with ACS without ST-segment elevation undergoing percutaneous coronary intervention. Current article demonstrates the results of recent clinical studies and the real clinical data regarding antiplatelet therapy in patients with coronary interventions. The indications for the use of P2Y12 platelet inhibitors in certain groups of patients are outlined. Treatment selection of the most effective and safe drugs in patients with ACS is highlighted according to the updated European guidelines.